Platform Preferences in Indonesia: Demographic Factors Shaping Online Behavior - Fakhri, Nurfitriany (HUMAN: South Asian Journal of Social Studies, 2025)
This study examines how demographic characteristics influence digital platform usage patterns among Indonesian internet users. Using data from 959 participants (66.3% female, 33.7% male), we analyzed the relationships between gender, occupational status, educational background, and engagement with various digital platforms. Results revealed significant demographic differences in platform preferences. Gender emerged as a substantial differentiating factor, with males showing higher engagement with news, gaming, and potentially problematic platforms, while females demonstrated greater usage of shopping and communication platforms. Occupational status significantly influenced digital behavior patterns, with employed individuals prioritizing professional tools like news sites and email, while university students exhibited higher engagement with entertainment and social media. Educational background primarily affected information-oriented platform usage, with higher education levels correlating with increased consumption of news and professional communication. Across all demographic segments, communication platforms dominated digital engagement, with participants typically spending 5-8 hours daily on instant messaging applications. Notably, minimal engagement with potentially problematic platforms was observed across all demographics. These findings provide empirical foundations for developing targeted digital literacy initiatives, informing policy decisions, and designing inclusive digital environments that acknowledge demographic differences in user behaviors. As digital technologies become increasingly integrated into Indonesian society, understanding these nuanced relationships between demographic characteristics and digital behaviors becomes essential for addressing emerging challenges and maximizing benefits across diverse population segments.